Weighted embedding theorems for radial Besov and Triebel-Lizorkin spaces - de Napoli, Pablo Luis (2016)
We study the continuity and compactness of embeddings for radial Besov and Triebel-Lizorkin spaces with weights in the Muckenhoupt class A∞. The main tool is a discretization in terms of an almost orthogonal wavelet expansion adapted to the radial situation.